7-Siloxy-Substituted Hexahydronaphthalene Derivatives: Samarium Diiodide Promoted Synthesis and Typical Reactions - Niermann, André; Reissig, Hans-Ulrich (Synthesis, 2020)
The samarium diiodide promoted reductive cyclization of a series of γ-aryl ketones with acetoxy, alkoxy, and siloxy groups in ortho-, meta-, and para-positions was investigated. Only precursors with p-acetoxy, p-tert-butoxy, or p-siloxy substituents furnished decent yields of the desired 7-oxy-1,2,3,4,6,8a-hexahydronaphthalene derivatives. The products were formed without contamination with the regioisomeric bicyclic products containing conjugated double bonds. Typical reactions exploiting the silyl enol ether moiety of the 7-(tert-butyldimethylsiloxy)-1,2,3,4,6,8a-hexahydronaphthalene derivative were performed, allowing stereoselective access to highly substituted hexahydro-, octahydro-, or decahydronaphthalene derivatives.
Keywords: dearomatization; ketyl; hexahydronaphthalene; radical; samarium diiodide; silyl enol ether